An empirical test on the impact of a gender diverse boardroom on agency cost and earnings management in China - Johera Ahmed, Shamima (2018)
Chinese firms have increasingly been in the news for their financial shenanigans. Because women are perceived to be more ethical and risk averse, cracking the corporate glass ceiling by promoting more women to the board seems to be a proper move to solve the governance problems of a male-dominated board. This paper seeks to address whether gender diversity on the board can reduce agency cost and earnings management on 883 listed firms in China for the period of 2008-2015. The results indicate that gender diversity on board does not reduce agency cost or earnings management in China. Other board characteristics like size, number of meetings, and independence are found to have a stronger influence in deterring fraud. As a minority group, women tend to adopt ‘male’ traits to negotiate with institutional barriers and become part of the group. This manner of coping negates the ‘added’ benefits that women can bring to the board.